2019
DOI: 10.1111/eth.12989
|View full text |Cite
|
Sign up to set email alerts
|

Great tits responding to territorial intrusions sing less but alarm more on colder days

Abstract: Bird song transmits information required to defend territories and attract mates. These functions contribute to fitness by affecting survival and reproductive success. Singing is also costly due to physiological costs. We used observational data to evaluate support for the hypothesis that lower temperatures result in decreased singing behaviour in wild great tits due to increased energy consumption during cold conditions required for thermoregulation. More than 6,500 simulated territorial intrusions were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Birds may face day‐to‐day changes in food availability or micro‐climatic factors affecting energy reserves, thus their production of high‐quality songs (Barnett & Briskie, 2007; Strauß et al, 2020; Thomas, 1999). Among years, song stability may vary with spring temperature, territory quality, breeding density or age (Botero et al, 2009; De Kort et al, 2009; Grava et al, 2012; Strauß et al, 2020). Importantly, males did not plastically shift their stability by changing song types, though song types differed in length, minimum frequency and stability (see also Logue et al, 2007; Slabbekoorn & den Boer‐Visser, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Birds may face day‐to‐day changes in food availability or micro‐climatic factors affecting energy reserves, thus their production of high‐quality songs (Barnett & Briskie, 2007; Strauß et al, 2020; Thomas, 1999). Among years, song stability may vary with spring temperature, territory quality, breeding density or age (Botero et al, 2009; De Kort et al, 2009; Grava et al, 2012; Strauß et al, 2020). Importantly, males did not plastically shift their stability by changing song types, though song types differed in length, minimum frequency and stability (see also Logue et al, 2007; Slabbekoorn & den Boer‐Visser, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Besides showing misestimated or undetected effects, caused by independent and opposing associations of the two components with a trait of interest (Moiron, Laskowski, & Niemel€ a, 2020;Van de Pol & Wright, 2009), this partitioning also led to valuable insights into the underlying mechanisms of aggressive signalling. While a within-individual effect indicates motivation or behavioural adjustments to environmental factors (Strauß et al, 2020), among-individual effects can result from genetic differences or early life conditions resulting in differing abilities to express certain behaviours (Bischoff et al, 2009).…”
Section: Personality or Context-dependent Motivation?mentioning
confidence: 99%
“…It is a model organism in behavioural ecology (Davies, Krebs, & West, 2012), commonly used to study the role of song in territory acquisition and maintenance (Akçay et al, 2020;Dabelsteen, McGregor, Shepherd, Whittaker, & Pedersen, 1996;Langemann et al, 2000) as well as within-and among-individual variation in behaviour, including territorial aggression (Araya-Ajoy & Dingemanse, 2014. Moreover, several studies have addressed the production and perception of song variation in relation to animal personality in this species (Amy et al, 2010;Jacobs et al, 2014;Strauß, Hutfluss, & Dingemanse, 2020). In previous studies, we have already shown that song output during simulated intrusions was negatively correlated with aggression in great tits, while seasonal plasticity in aggressiveness was repeatable, heritable and age dependent (Araya-Ajoy & Dingemanse, 2014.…”
mentioning
confidence: 99%
“…Calling more than necessary is a waste of energy, leads flock mates to waste energy on unnecessary predator avoidance or hypervigilance, and in extreme cases leads to anti‐predator (alarm and mobbing) calls being ignored (Beauchamp & Ruxton, 2007; Flower et al, 2014). Posing an indirect cost, anti‐predator calling reduces the opportunity for singing (Strauss et al, 2020). The most successful social groups, then, are those that anti‐predator call only when the threat is imminent and continue to forage, nest, sing, etc., when it is not (Beauchamp & Ruxton, 2007).…”
Section: Introductionmentioning
confidence: 99%